Improvement of rheology and mechanical properties of PLA/PBS blends by in-situ UV-induced reactive extrusion. (27th October 2022) - Chang, Fu-Lu; Hu, Bin; Huang, Wei-Tao; Chen, Lun; Yin, Xiao-Chun; Cao, Xian-Wu; He, Guang-Jian
Abstract: Blending with biodegradable poly (butylene succinate) (PBS) is an effective way for improving the performance of PLA. However, the property of the blends is not significantly improved due to poor compatibility between the two polymers. Herein, we propose a simple method to prepare biodegradable PLA/PBS blends successfully by UV-induced reactive extrusion. Multifunctional monomer trimethylolpropane tri-acrylate (TMPTA) is used as chain extender to react with PLA and PBS to generate graft copolymers at the PLA/PBS interface. Addition of glycidyl methacrylate (GMA) could further promote the graft reaction, thus increase the compatibility and the mechanical properties of the blends. The occurrence of the long chain branched reaction between the PLA and PBS is evidenced by the rheological results and Fourier-transform infrared spectroscopy analysis. Appropriate amount of GMA reduces the size of dispersed PBS phase and enhances the interfacial strength. The crystallization of PLA is effectively improved, as evidenced by the increased cool crystallization peak and apparent enhancement crystallinity. Ultimately, PLA/PBS blends compatibilized with GMA/TMPTA exhibit a remarkable improvement in elongation at break of 341%, notched impact strength and a preferable maintenance of 50 MPa in tensile strength. Graphical abstract: Image 1 Highlights: The synergistic effect of GMA and TMPTA plays a good role in compatibilization. Chain extension and crystallization of PLA/PBS blends are realized simultaneously. This strategy can maintain good mechanical properties of composites.